Attitudes toward Science Based on Analysis and Correlation: Learning Enjoyment & Leisure Interest on Science - Tanti Tanti; Dwi Agus Kurniawan; Nugroho Kurniawan; Lika Anggraini (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
This study aims to investigate attitudes towards science in junior high school students, which are assessed based on 2 attitude indicators: (1) enjoyment in science lesson & (2) leisure interest in science. In addition, measurements were also made regarding the relationship between the two indicators of attitude. Research method: This research is survey research. The results of the data came from an attitude questionnaire consisting of indicators (1) enjoyment in science lesson and (2) leisure interest in science. The sample consisted of 2815 Secondary School students in Jambi Province, Indonesia. Finding: The results showed positive results, based on the investigation concluded that for indicators: (1) enjoyment in science has a good category with a percentage of 48.1%, (2) leisure interest in science has a fairly good category with a value: 47.2% and This indicator leads to a positive trend supported by a positive attitude with a greater good value: 38.4%, while for the analysis of the correlation between the two indicators shows a positive correlation with a sig: 0,000 (<0.05) and has a strong degree of correlation indicated by the value "Pearson Correlation": 0.716. Conclussions: from these results it can be concluded that students' attitudes towards science based on investigations & descriptive analysis of indicators show positive attitudes and tend to be good, and based on analysis of the relationship between the two attitude indicators also show positive results, so it is concluded overall attitudes towards science at Junior high school students in Jambi, Indonesia have a positive attitude and are categorized well.